Efficacy of PDT in vulvar LS treatment based on immunohistochemical analysis of CD3, CD4, CD8, CD57, Granzyme B and Fascin expression - Olejek, Anita; Olszak-Wąsik, Katarzyna; Stęplewska, Katarzyna; Horák, Stanisław; Zamłyński, Jacek; Kozak-Darmas, Iwona; Gabriel, Andrzej (Menopause Review/Przegląd Menopauzalny, 2013)
Background: Lichen sclerosus (LS) is an immune-mediated chronic dermatosis of perimenopausal women. Inflammatory infiltration has been suggested as a potential cause of LS changes in epidermis and dermis. Photodynamic therapy (PDT) is a specific noninvasive treatment based on detection and subsequent selective destruction of LS-affected tissues that are marked by a photosensitizer. Immunomodulatory and cytotoxic effects of PDT are responsible for inducing several immunologic reactions which leads to inflammatory condition improvement. The aim of the study was to determine the efficacy of photodynamic therapy for genital LS in correlation to protein expression involved in inflammatory infiltration – CD3, CD4, CD8, CD57, Granzyme B and Fascin. Material and methods : A group of patients has been treated for active LS disease, diagnosis was histologically confirmed in skin biopsies. The skin biopsies were taken and analyzed with antibodies: CD3, CD4, CD8, CD57, Granzyme B and Fascin before and after PDT treatment. Results: The study shows the efficacy of PDT in LS treatment including changes to CD3, CD4, CD57, Fascin, Granzyme B and the lymphocytic infiltration in skin sections. The proliferation index of CD4 did not differ before and after PDT. Conclusions: The PDT is a very effective therapeutic method in LS treatment.